HIGH PERCENTAGE OF RARE EARTH ELEMENT CONNECTION WITH THE ACCUMULATION SEDIMENT AS RESPONSE LONGSHORE CURRENTS IN THE BELITUNG WATERS - Delyuzar Ilahude; Maman Surachman (Marine Geological Institute of Indonesia, 2015)
The study area is geographically located in the West coast of Belitung island at coordinates 105o48'00